Examining Motor Anticipation in Handwriting as an Indicator of Motor Dysfunction in Schizophrenia - Crespo Cobo, Yasmina; Kandel, Sonia; Soriano, María Felipa; Iglesias-Parro, Sergio (Frontiers in Psychology, 2022)
Dysfunction in motor skills can be linked to alterations in motor processing such as the anticipation of forthcoming grapho-motor sequences. We expected that the difficulties in motor processing in schizophrenia would be reflected in a decrease of motor anticipation. In handwriting, motor anticipation concerns the ability to write a letter while processing information on how to produce the following letters. It is essential for fast and smooth handwriting; i.e., for the automation of grapho-motor gestures. In this study, we examined motor anticipation by comparing the kinematic characteristics of the first l in the bigrams ll and ln written on a digitiser. Previous studies indicated that the downstroke duration of the first l is modulated by the anticipation of the local constraints of the following letter. 24 adult individuals with diagnosis of schizophrenia and 24 healthy adults participated in the study. The classic measures of duration (sec), trajectory (cm) and dysfluency (velocity peaks) were used for the kinematic analysis of the upstroke (US) and downstroke (DS). In the control group, the duration of the downstroke of the l was longer in ln than ll (US: ln = ll; DS: ln> ll) whereas no differences were found for the group with schizophrenia. Likewise, the control group showed a longer DS trajectory for the l of ln than ll in downstrokes, while the group of patients failed to show this effect. These results suggest that the motor alterations in patients with schizophrenia could also affect their ability for motor anticipation.